Experimental and modeling research on thermal radiation characteristics of glowing contact in electrical fires - Jing Zhang; Wenhui Ju; Tao Chen; Guofeng Su; Changzheng Li; Wenzhong Mi (Case Studies in Thermal Engineering)
Poor electrical contact is one of the main reasons for electrical fires. Glowing contact triggered by poor contact can reach high temperature on electrical wires. The peak temperature can be up to 1,000 °C. Thus, the radiative thermal hazards of glowing contact cannot be ignored. In this study, the radiative heat flux of glowing contact is measured and quantified. A thermo-electrical Multiphysics model of glowing contact describes the distribution of the radiative heat intensity. An empirical model of radiation heat flux of glowing contact is obtained by two-step fitting based on the simulation data. Results demonstrate that the radiative heat flux of glowing contact decreases with distance and increases with time. PVC insulation layers are exposed to high fire risk when the distance between glowing contact and PVC is within 7 mm. Simulation results show that the contour lines of radiation are approximately elliptical due to the slender cylindrical glowing oxide bridge. The two-dimensional Gaussian distribution is applied to fit the simulation data. It can be utilized for studies on glowing contact’s ignition characteristics.